Analysis of load-induced top-down cracking initiation in asphalt pavements using a two-dimensional microstructure-based multiscale finite element method. (July 2019) - Sun, Yiren; Du, Cong; Zhou, Changhong; Zhu, Xiaoxu; Chen, Jingyun
Highlights: Mechanisms of top-down cracking initiation for asphalt pavements were analyzed through a multiscale finite element model. Material properties on two scales were incorporated in computation and linked through homogenization. A digital image processing technology was employed to develop the local-scale representative volume element model. Two typical asphalt pavement structures were considered. Abstract: Load-induced top-down cracking is one of the major types of asphalt pavement deterioration; however, its initiation mechanisms have not been fully understood so far, which makes it very difficult to effectively consider this failure pattern in the pavement design procedures. To address this issue, the present study developed a two-dimensional microstructure-based multiscale finite element model, in which material properties on two physical length scales, i.e., the local (mixture level) and global (pavement level) scales, were incorporated in the computation and linked through a homogenization process. A digital image processing (DIP) technology was employed to develop the two-dimensional local-scale representative volume element (RVE) model that considered the realistic heterogeneous microstructure of asphalt concrete (AC), and a bilinear cohesive zone model was applied to simulating the local-scale damage initiation and evolution in the RVEs. Two typical pavement structures, with cement-treated base (CTB) and granular base (GB) respectively, were taken into account to interpret the influence of the global-scale pavement configurations on top-down cracking performance. The results showed that the significant near-surface transverse tensile stress just outside the tire edge could be the primary cause of the top-down cracking. For the pavement with CTB, the top-down cracking was the predominant type of fatigue failure, whereas for the pavement with GB, the bottom-up cracking was the main pattern of fatigue failure. Besides, as the temperature increased, more damage was induced under the same traffic loading due to the reduced tensile strength of AC. It was also found on the local scale that the significant tensile stress within the mortar matrix phase probably acted as the driving force of the microcrack initiation and propagation and the effects of the shear traction on the damage evolution in the AC layer increased with the temperature.